2021
DOI: 10.7759/cureus.12721
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinoma With Calcification: Case Report of Calcifying Basal Cell Carcinoma and Review of Calcinosis Cutis Associated With Basal Cell Carcinoma

Abstract: Basal cell carcinoma is the most common cutaneous neoplasm. Calcinosis cutis is the deposition of calcium within the dermis. An 80-year-old man presented with a pearly nodule on his left nasal ala; a shave biopsy confirmed the diagnosis of a nodular basal cell carcinoma with calcinosis cutis, which was removed with Mohs micrographic surgery. The incidence of basal cell carcinoma with calcinosis cutis as well as the classification, identification, and potential origin of calcium deposits in basal cell carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Calciphylaxis is associated with a particularly grim prognosis [1]. A list of diagnoses and pathologic processes associated with these CC subtypes is detailed elsewhere (Table 1) [1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Though our patient did not have autoimmune titers or recent serum calcium or phosphate levels, he also did not have clinical findings which would suggest a CTD or other systemic process.…”
Section: Discussionmentioning
confidence: 99%
“…Calciphylaxis is associated with a particularly grim prognosis [1]. A list of diagnoses and pathologic processes associated with these CC subtypes is detailed elsewhere (Table 1) [1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Though our patient did not have autoimmune titers or recent serum calcium or phosphate levels, he also did not have clinical findings which would suggest a CTD or other systemic process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, benign tumours associated with hair follicles such as pilomatricomas, trichilemmal cysts, and trichoepitheliomas also display calcinosis cutis 2 . Even when initial superficial histological sections of a tissue specimen revealed only calcium deposition in the dermis, malignant or benign tumours with calcinosis cutis could be found in deeper section 1 . Therefore, we made deeper sections and carefully reconfirmed that there was no histological finding of BCC or other tumours.…”
Section: Case Reportmentioning
confidence: 99%
“…Given the patient's age, location of the skin lesions, and dermoscopic findings, BCC would be an important differential diagnosis in this case. It has been reported that the calculated incidence of BCC with calcinosis cutis is 14% 1 . In addition, benign tumours associated with hair follicles such as pilomatricomas, trichilemmal cysts, and trichoepitheliomas also display calcinosis cutis 2 .…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations